2022
DOI: 10.3389/fimmu.2022.926044
|View full text |Cite
|
Sign up to set email alerts
|

The Complement System and ANCA Associated Vasculitis in the Era of Anti-Complement Drugs

Abstract: ANCA (anti-neutrophil cytoplasmic antibody)-associated vasculitis (AAV) is the condition in which ANCA, as an autoantibody, is associated with the pathogenesis of vasculitis in small blood vessels, mainly in the ear, nose, throat, kidney, lung, and nerves. These diseases are important because they can be fatal due to renal failure and pulmonary hemorrhage if not promptly and appropriately treated. Recently accumulated evidence has shown that C5a produced by the complement alternative pathway primes neutrophils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Standard remission-induction treatment for ANCA-associated vasculitis (AAV) consists of glucocorticoids and immunosuppression (typically rituximab and/or cyclophosphamide), with subsequent maintenance therapy with tapering glucocorticoids. 2,3 Recently the role of the alternate pathway of complement in AAV has been uncovered, 4,5 mediated by C5a, which primes neutrophils for activation by ANCA. 6 Avacopan, a C5aR antagonist acts on this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Standard remission-induction treatment for ANCA-associated vasculitis (AAV) consists of glucocorticoids and immunosuppression (typically rituximab and/or cyclophosphamide), with subsequent maintenance therapy with tapering glucocorticoids. 2,3 Recently the role of the alternate pathway of complement in AAV has been uncovered, 4,5 mediated by C5a, which primes neutrophils for activation by ANCA. 6 Avacopan, a C5aR antagonist acts on this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The PMX line of C5aR1 antagonists in particular have proven fruitful for the ongoing drug development in this class, with some of the members of this family having entered clinical development and evaluation 21 . At this point, the recently approved C5aR1 antagonist avacopan is the only orally bioavailable complement inhibitor in the clinic, 22 while other oral complement modulators are in late‐stage development (Table 1). 23,24 …”
Section: Target Inn (Brandname) Company Type Status Indicationmentioning
confidence: 99%
“…20 The PMX line of C5aR1 antagonists in particular have proven fruitful for the ongoing drug development in this class, with some of the members of this family having entered clinical development and evaluation. 21 At this point, the recently approved C5aR1 antagonist avacopan is the only orally bioavailable complement inhibitor in the clinic, 22 while other oral complement modulators are in late-stage development (Table 1). 23,24 Perhaps the most prominent example for a drug discovery and development process in the complement field that continues to involve partners from the academic, clinical, and industrial branch is the compstatin family of C3 inhibitors, which was identified in the academic lab of John Lambris at the University of Pennsylvania.…”
mentioning
confidence: 99%
“…Two principal antigens on neutrophils—namely, proteinase 3 (PR3) and myeloperoxidase (MPO)—provide epitopes for ANCA binding, promoting endothelial damage and vascular inflammation, culminating in necrotizing vasculitis [ 5 , 6 , 7 ]. Innate immunity with complement system activation is increasingly recognized in the pathogenesis of AAV and as an attractive therapeutic target [ 8 , 9 ]. Although C-reactive protein (CRP) was thought to be a passive, nonspecific marker of inflammation, recent studies indicate that CRP plays a key role in the innate immune system by recognizing pathogens and altered self-determinants [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%